COMMUNITY EMPOWERMENT IN SERUT VILLAGE ON CLIMATE CHANGE ADAPTATION AND MITIGATION - Permana Arief Mardika; Ahmad Sarwadi; Retno Widodo Dwi Pramono (Jurnal Teknosains, 2017)
Based on Regulation of Indonesian Environment Ministry number 19/2012 about Climate Village (Proklim) Program, Serut Village is designated as Climate Village in 2012 because of the effort on climate change adaptation and mitigation. This success is not separated from the community empowerment efforts after Bantul earthquake in 2006. This research aims to describe the community empowerment on climate change adaptation and mitigation then identify factors inﬂ uence community empowerment. This research method used case study with single case using qualitative descriptive approach. The research results indicate that the community empowerment has occured simultaneously and unnoticed caused by the earthquake. Community empowerment is reﬂ ected in many sectors, such as development of organic farming, management of livestock farming with communal cages, community base litter management, disaster response, greening and water resources management. Factors that inﬂ uence the process of community empowerment are natural conditions; society culture, norm, and community self-help; local leader; and government.